ENT600: All purposes casing (APC) / Siti Amira Hamdan … [et al.] - Hamdan, Siti Amira; Abd Rahim, Ain Adilla; Bronny, Belinda Gabriella; Mohd Faiz, Muhammad Nazran; Lapok, Hafidah (2018)
The product of All Purpose Casing (APC) was introduced in order to satisfied the problems arised when using the Touch n' Go cards. The APC is designed to connect a special chip with Touch n' Go card. The connectivity between the chip and the card will allow user easily check their routes fare, transaction history, currents balace and usage of e-payment via mobile application. . The APC is a casing where the users used it without worry of the wavelengths messed up the scanner. The APC products are limited only for flagship phone casing which only target for flagship phone users and it is not water proof casing. The research and development-(R&D) process is done for ideation stage through idea generation, idea screening and market survey. In idea generation, the product proposes is to ease the struggle in handling the Touch n' Go card. Thus," the Touch n' Go phone casing came to minds and it becames the main idea of the new product development project. The features of APC product are allow e-payment transaction, on the go online payment and quick and easy transaction. Due to installment of Touch n' Go card inside the casing, it allow the users to make on the go online payment. For example, the payment of goods at counter. Besides, APC product will make the user experiences in quick and easy transaction than the struggles in finding cards in bags and wallets. The APC also allow the e-payment transaction where by the users needs to pay bills for utilities or phone bills. In concept testing, beta testing method was used in this new product development. Beta testing is a method where by trial version was released and the tester will used the trial version in order to observe either the product is success or not. After the testing was done, the tester will gave feedback of the product to the company for the trial version product. The market testing was aim for students and public transport user. The results shows that 95% of the students will consider to used APC product as the product can alert the users of their balance in Touch n' Go card on their smartphone. In conclusion, the APC product is used better than cash carried and the product is tempted enough to attract the users to used the APC product due to the convenient features and trendy design. APC product also can make users experience the better technology arid mobile application than Touch n' Go card.